Numerical study on the effect of rim seal slot filleting on turbine endwall cooling - Xinchun Li; Na Wei; Liuliu Shi; Eryun Chen (AIP Advances)
In this study, the effect of rim seal slot filleting on turbine endwall film cooling performance is numerically investigated. For comparison with the baseline case, five different fillet radius and width (R/W) ratios are adopted, i.e., R/W = 1.25, 2.5, 3.75, 5, and 6.25. The results indicate that an improvement up to 10% in overall film cooling effectiveness can be achieved with smaller fillet radii. However, this effect diminishes as the fillet radius increases and becomes negative at R/W = 6.25. By examining the contours of the film cooling effectiveness, a prominent inclined strip can be observed across the blade passage. The analysis indicates that the pressure-side leg horseshoe vortex is the primary factor contributing to the variation in the film cooling performance. Furthermore, the film cooling effectiveness can be slightly improved near the suction side of the blade leading edge as the result of the suppression of endwall separation in this region. The rim seal slot filleting eliminates the slot leakage separation, which, in turn, expedites the endwall cooling flow. Eventually, pressure-side leg horseshoe vortex is weakened and the performance of the film cooling is improved. As the fillet radius continues to increase, the through-flow area for the cooling flow enlarges, resulting in a gradual decrease in the film cooling performance.